Frankenstein's daughter - Cunha, Richard; Barrie, H. E.; Ashley, John, 1934-1997; Layton Film Productions, Inc.; Cinetel Films ([Los Angeles, CA] : Layton Film Productions Inc., 1958)
--
Originally released as a motion picture in 1958.
John Ashley, Sandra Knight, Donald Murphy, Sally Todd, Harold Lloyd, Jr., Page Cavanaugh and his Trio.
Cinematographer, Meredith Nicholson; editor, Everett Dodd; music, Nicholas Carras.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Sexual harassment -- Drama; Immortalism -- Drama; Frankenstein, Victor (Fictitious character); Popular music -- United States -- 1951-1960.; Monster films; Feature films; Internet videos; Streaming video